PENENTUAN KONDISI OPERASI OPTIMAL PADA PENYULINGAN MINYAK NILAM - Setyoko, Bambang (TEKNIK, 2007)
Patchauly distillation is a process where oil can exctract from patcahauly’s leaf, branch, stem and root.Patchauly’s branch, stem and root had randement lower than patchauly’s leaf.This research used vacuum distillation methode at low temperature and low pressure. The experiment wasdone repeatedly at different pressure and temperature. Than experiment’s data was analysed in laboratoryand compared than standard.The highest purity of patchauly oil is 28 %, efficiency 2,5 % at temperature 80oC and used pressure -50 cmHg